2020
DOI: 10.1097/gme.0000000000001558
|View full text |Cite
|
Sign up to set email alerts
|

The effects of a new, improved Chinese medicine, Gengnianchun formula granules, on hot flushes, depression, anxiety, and sleep in Chinese peri- and postmenopausal women: a randomized placebo-controlled trial

Abstract: Objective: The aim of the study was to investigate the effectiveness and safety of a new, improved herbal formula of a traditional Chinese medicine, improved Gengnianchun (I-GNC), on hot flushes, depression, anxiety, and sleep in peri- and postmenopausal women in China. Methods: A randomized, single-blind, placebo-controlled trial of peri- and postmenopausal women with Kupperman Index (KMI) scores of 15 or higher was conducted for 12 weeks. Hot flush fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…Herbal formula with several herbal medicines modulates more targets compared with single compound herbal preparation. Previous studies report activities of TCM formula such as Danzhi Xiaoyao powder, Gengnianchun, and Yixin Ningshen tablet against depression (Wu et al, 2020;Zhang et al, 2020;Zhu et al, 2020). The findings of our study show that HLJDD improves depressive disorders primarily through modulation of tryptophan metabolism, dopaminergic synaptic function, and cAMP, FoxO and calcium signaling pathways.…”
Section: Discussionsupporting
confidence: 60%
“…Herbal formula with several herbal medicines modulates more targets compared with single compound herbal preparation. Previous studies report activities of TCM formula such as Danzhi Xiaoyao powder, Gengnianchun, and Yixin Ningshen tablet against depression (Wu et al, 2020;Zhang et al, 2020;Zhu et al, 2020). The findings of our study show that HLJDD improves depressive disorders primarily through modulation of tryptophan metabolism, dopaminergic synaptic function, and cAMP, FoxO and calcium signaling pathways.…”
Section: Discussionsupporting
confidence: 60%
“…GNC is a formula mainly applied clinically to alleviate perimenopausal syndrome and ovarian aging-related diseases, such as Alzheimer's disease, which was previously widely studied by our group. 12,13,29,30 Ovarian aging shares similar phenotypes with DOR, as both feature a decreased follicle pool and hypogonadal endocrine status. Thus, GNC has also been used to treat patients with DOR.…”
Section: Discussionmentioning
confidence: 99%
“…8 Traditional Chinese medicine (TCM) has promising effects on treating gynecological endocrinology dysfunctions. [9][10][11] Gengnianchun (GNC) is a previously widely reported formula in the treatment of menopausal syndrome 12 and menopause-related diseases such as Alzheimer's. 13 According to TCM theories, DOR shares a similar etiology with menopause, which is deficient in the kidney.…”
Section: Introductionmentioning
confidence: 99%
“…The moxibustion study reported no serious AEs and a minor AE, thirst, occurred for one participant. Among the two studies of Chinese herbal medicine, one study reported no serious AEs or AEs 22 , and one study reported one serious AE, dysplasia of squamous epithelium, which was thought not to be related to the study trial medication 18 .…”
Section: Resultsmentioning
confidence: 99%
“…The search process results of our systematic review are presented in Figure 1. This review focused on a total of 9 trials [14][15][16][17][18][19][20][21][22] of the effects of traditional East Asian medicine (TEAM) on menopausal transition symptoms (hot flashes, sleep, mood, pain, cognitive concerns), representing a total of 811 participants from 7 countries. One trial examined two interventions separately 18 .…”
Section: Resultsmentioning
confidence: 99%